Acting on the invisible: Computational tools and community action in the landscapes of air quality. (June 2020) - Mondor, Christine Ann; Azel, Nicolas
This article proposes that designers and planners can better manage wicked problems by developing a strategic alignment of computational technology with a theory of change. Together with an understanding of the most effective places to intervene in a system, designers' informed use of technology enables them to orchestrate community action and leverage large-scale environmental change. Aligning technology with a theory of change deepens the relevance of computational tools and suggests that technologies or tools that augment one's ability to perceive, understand relevance, or prioritize raise the potential for action ; technologies or tools that aggregate information on collective beliefs or actions help to build a community of concern ; and technologies that elevate community capacity and create a sense of identity can contribute to the long-term transformation of values . Through a case study, this article demonstrates a nested approach to computation, which enhances public awareness and enables action in a small community which is trying to manage an extra-territorial problem of air quality. This article also proposes that while computational tools have extended the reach and effectiveness of advocacy, designers should continue to push for expanded application. By aggregating lessons learned from technological networks, such as the emerging clean air network described in this article, we can add another socio-ecological dimension to the practices of landscape and urbanism.